Exploring the various effects of Cu doping in hydroxyapatite nanoparticle - Alireza Noori; Mahdieh Hoseinpour; Sedighe Kolivand; Nasrin Lotfibakhshaiesh; Somayeh Ebrahimi‐Barough; Jafar Ai; Mahmoud Azami (Scientific Reports, 2024)
Abstract Adding foreign ions to hydroxyapatite (HAp) is a popular approach for improving its properties. This study focuses on the effects of calcium substitution with copper in HAp. Instead of calcium, copper ions were doped into the structure of hydroxyapatite nanoparticles at 1%, 3%, and 5% concentrations. XRD analysis showed that the amount of substituted copper was less than needed to generate a distinct phase, yet its lattice parameters and crystallinity slightly decreased. Further, the results of degradation tests revealed that copper doping in hydroxyapatite doubled calcium ion release in water. The incorporation of copper into the apatite structure also boosted the HAp zeta potential and FBS protein adsorption onto powders. According to antibacterial investigations, a concentration of 200 mg/ml of hydroxyapatite containing 5% copper was sufficient to effectively eradicate E. coli and S. aureus bacteria. Furthermore, copper improved hydroxyapatite biocompatibility. Alkaline phosphatase activity and alizarin red tests showed that copper in hydroxyapatite did not inhibit stem cell differentiation into osteoblasts. Also, the scratch test demonstrated that copper-containing hydroxyapatite extract increased HUVEC cell migration. Overall, our findings demonstrated the utility of incorporating copper into the structure of hydroxyapatite from several perspectives, including the induction of antibacterial characteristics, biocompatibility, and angiogenesis.